The influence of physical exercise on adolescents’ externalizing problem behaviors: mediating effects of parent–child relationships, self-esteem, and self-control - Cui, Long; Xing, Yumei; Gu, Jixing; Zhou, Hao; Zhang, Lin; Bu, Yifeng (Frontiers in Public Health, 2024)
Background Externalizing problem behaviors can significantly and negatively impact adolescents’ learning, daily life, and future socialization. While physical exercise is believed to inhibit adolescents’ externalizing problem behaviors, the extent of its effect and the mediating mechanisms remain unclear. Methods This study is based on data from the 2018 China Family Panel Studies (CFPS). The CFPS project employed the Externalizing Problem Behaviors Scale (EPBS), the Rosenberg Self-Esteem Scale (RSES), and the Self-Control Scale (SCS) to measure adolescents’ externalizing problem behaviors, self-esteem, and self-control. Additionally, physical exercise was measured by collecting data on the time and frequency of adolescents’ physical exercise. Parent-child relationships were evaluated using a composite variable that included four dimensions: frequency of quarrels, frequency of heart-to-heart talks, parental awareness of their children’s whereabouts, and children’s trust in their parents. Based on data collection and variable construction, this study employed multiple linear regression, propensity score matching, and quantile regression to analyze the impact of physical exercise on adolescents’ externalizing problem behaviors and the heterogeneity of these effects. Additionally, the Bootstrap mediation effect test was employed to explore the mediating roles of parent-child relationships, self-esteem, and self-control in this process. Results The analysis demonstrates that physical exercise significantly inhibits adolescents’ externalizing problem behaviors (β = −0.095, p < 0.01), although the effect varies significantly among different populations. Compared to males (β = −0.077, p < 0.1), rural residents (β = −0.065, p > 0.1), individuals with poorer family economic status (β = −0.080, p < 0.1), and those with more severe problem behaviors (τ = 0.75, β = −0.086, p < 0.05), physical exercise yields a more pronounced inhibitory effect on females (β = −0.113, p < 0.01), urban residents (β = −0.134, p < 0.01), individuals with better family economic status (β = −0.115, p < 0.01), and those with milder problem behaviors (τ = 0.25, β = −0.112, p < 0.01). Furthermore, through enhancements in parent-child relationships (CI: -0.015; -0.002), self-esteem (CI: -0.019; -0.003), and self-control (CI: -0.055; -0.025), physical exercise indirectly mitigates adolescents’ externalizing problem behaviors. Conclusion Physical exercise significantly reduces adolescents’ externalizing problem behaviors, with effects differing across various groups. Parent-child relationships, self-esteem, and self-control mediate this relationship, underscoring the positive influence of exercise on adolescent behavior.